Efeito do ultrassom terap??utico na regenera????o muscular e na express??o de fatores miog??nicos em m??sculo esquel??tico de rato ap??s les??o. - Rocha, Dayane Aparecida Mesquita (2010)
ltrasound has been used for the clinical treatment of a number of inflammatory musculoskeletal conditions, but its efficacy has not yet been proven. The aim of the present study was to assess the effect of therapeutic ultrasound on the regeneration rat skeletal muscle following cryoinjury and determine its role in the expression of myogenic factors (MyoD and myogenin). One hundred Wistar rats were separated into a control group (n=10), sham group (n=10), cryoinjured group without treatment (n=40) and cryoinjured group treated with ultrasound (n=40). In the groups with cryoinjury, the injury was performed on the left tibialis anterior muscle. Among the treated animals, the muscles were submitted to daily one-minute applications of pulse ultrasound at a frequency of 1 MHz and intensity of 0.8 W/cm2. The animals in the cryoinjury and ultrasound groups were assessed after one, seven, 14 and 21 days. Body weight was determined in all evaluation periods. The muscles were morphologically analyzed using hematoxylin-eosin staining. The expression of myogenic factors (MyoD and myogenin) was determined using real-time PCR. The morphological and semi-quantitative analysis of edema, inflammatory process, myonecrosis and the presence of new fibers revealed that treatment with ultrasound promoted a reduction in the acute inflammatory process on Day 1 following injury, but did not affect the other phases of muscle repair. Ultrasound did not alter the expression of mRNA of MyoD or myogenin in any evaluation period. In conclusion, pulsed ultrasound did not accelerate the muscle regeneration process or affect the expression of proteins involved in myogenesis under the conditions analyzed. However, ultrasound proved effective in modulating the acute inflammatory process in rat skeletal muscle following cryoinjury.